2021
DOI: 10.3389/fimmu.2021.686846
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Receptor Mediates the Activation of Chitooligosaccharides on Blunt Snout Bream (Megalobrama amblycephala) Macrophages

Abstract: Chitooligosaccharide (COS) is an important immune enhancer and has been proven to have a variety of biological activities. Our previous research has established an M1 polarization mode by COS in blunt snout bream (Megalobrama amblycephala) macrophages, but the mechanism of COS activation of blunt snout bream macrophages remains unclear. In this study, we further explored the internalization mechanism and signal transduction pathway of chitooligosaccharide hexamer (COS6) in blunt snout bream macrophages. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…COS has smaller molecular weight (MW), lower degree of polymerization (DP), and good water solubility which chitosan does not possess [ 13 , 14 , 15 ]. Similar to other natural carbohydrate [ 16 , 17 ], COS has been shown to have good immunogenicity and anti-inflammatory activity in vitro [ 18 , 19 , 20 ] and in vivo [ 21 , 22 , 23 ], and is expected to be a good natural anti-inflammatory drug to prevent and treat endotoxemia. The anti-inflammatory activity of COS is related to its structural parameters, including MW, DP and degree of acetylation (DA) etc.…”
Section: Introductionmentioning
confidence: 99%
“…COS has smaller molecular weight (MW), lower degree of polymerization (DP), and good water solubility which chitosan does not possess [ 13 , 14 , 15 ]. Similar to other natural carbohydrate [ 16 , 17 ], COS has been shown to have good immunogenicity and anti-inflammatory activity in vitro [ 18 , 19 , 20 ] and in vivo [ 21 , 22 , 23 ], and is expected to be a good natural anti-inflammatory drug to prevent and treat endotoxemia. The anti-inflammatory activity of COS is related to its structural parameters, including MW, DP and degree of acetylation (DA) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Immunopotentiators, based on recent successes in both laboratory and clinic, are considered a viable option for controlling bacterial diseases ( 9 , 10 ). Some antimicrobial peptides (AMPs) have good immune regulation function, so they can also be used as immunopotentiators.…”
Section: Introductionmentioning
confidence: 99%
“…They also proved that the internalization of COS depends on the mannose receptor to some extent [ 33 ]. Aotian Ouyang et al systematically explored the mechanism of action of mannose receptors (MR) in COS internalization and concluded that MR and TLR4 act synergistically, although they used blunt-snout-bream macrophages [ 15 ]. Although MR has been studied more frequently, COS can still be internalized and show its activity after the inhibition of the MR, which is consistent with the increased expression of multiple receptors in the RNA-seq results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COS can alleviate enteritis damage in mice or turbot [ 13 , 14 ]. There is also some research suggesting that COS could modulate macrophage polarization in mice or blunt-snout bream [ 15 , 16 ]. Our previous work demonstrated the anti-inflammatory activity of COS in vitro and in vivo and found that COS with a degree of acetylation (DA) = 12% was the best.…”
Section: Introductionmentioning
confidence: 99%